Sintering temperature dependent micro and macro mechanical properties of Si3N4f/SiO2 composite materials. Issue 17 (1st December 2019) - Yang, Xuejin; Li, Bin; Li, Duan; Shao, Changwei; Zhang, Changrui; Yang, Lingwei; Zou, Chunrong; Liu, Kun
Abstract: Wave-transparent materials for the high temperature use require highly reliable mechanical properties and excellent anti-oxidation performance. This study reports the densification, interfacial evolution, micro and macro mechanical properties of Si3 N4f /SiO2 composites sintered at 800–1200 °C. The results show that significant shrinkage of silica matrix at 1100–1200 °C helps improve the density of Si3 N4f /SiO2 composites, but also leads to an obvious reduction of mechanical properties. The bending strength of composites sintered at 800–1000 °C reaches 166.5–174.0 MPa, but linearly decreases to 102.5 MPa at 1100 °C and 19.8 MPa at 1200 °C. Similarly, fracture toughness also experiences a linear decline, decreasing from 7.0 to 7.2 MPa m 1/2 at 800–1000 °C to around 3.7 MPa m 1/2 at 1100 °C and 1.0 MPa m 1/2 at 1200 °C. As to the high-temperature performance, the in-situ bending strength at 1200 °C of the 800–1000 °C sintered composites is lower than 75Mpa. Interfacial diffusion cooperated with the uneven shrinkage of silica matrix is regarded as major reasons to the degradation of composites sintered or tested at over 1100 °C, for that they can lead to an increase of fiber-matrix interfacial bonding and trigger the generation of internal stresses and even visible cracks.